ANAK YATIM SEBAGAI MUSTAHIK ZAKAT - Sainul, Ahmad (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2019)
Mustahik zakat is the people who are entitled to receive the assets of sakat issued by zakat payers. Mustahik zakat it self there are eight groups of indigent people, poor people, administrators of zakat, the Mu'allaf who are persuaded by their hearts, to (liberate) slaves, people who owe for the cause of Allah and for those who are on the journey, as a duty prescribed by Allah, and Allah is Knower, Wise.The law of making orphans as mustahik zakat can be seen from two sides as follows: Poor orphaned children, orphans who live in poor condition, especially fakir, it is permissible to get a share of zakat. If orphans have assets or are rich or have rich families who take care of them, the group of orphans may not be made as recipients of zakat because the orphans have property, while people who have unauthorized assets become mustahik zakat.